2022
DOI: 10.3389/fvets.2022.855933
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Homozygous Regions With Adverse Effects on the Five Economic Traits of Duroc Pigs

Abstract: Runs of homozygosity (ROH) are widely used to estimate genomic inbreeding, which is linked to inbreeding depression on phenotypes. However, the adverse effects of specific homozygous regions on phenotypic characteristics are rarely studied in livestock. In this study, the 50 K SNP data of 3,770 S21 Duroc (American origin) and 2,096 S22 Duroc (Canadian origin) pigs were used to investigate the harmful ROH regions on five economic traits. The results showed that the two Duroc lines had different numbers and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Demographic events like population bottlenecks, genetic drift, and inbreeding primarily contribute to the formation of ROH [ 10 , 11 ]. These homogenous DNA segments are instrumental in the analysis of inbreeding in livestock species [ 12 , 13 , 14 ]. In livestock, the length of ROH segments serves as an indicator of the level of inbreeding, with longer ROH segments denoting recent inbreeding events and shorter segments indicating inbreeding that occurred earlier in the generations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic events like population bottlenecks, genetic drift, and inbreeding primarily contribute to the formation of ROH [ 10 , 11 ]. These homogenous DNA segments are instrumental in the analysis of inbreeding in livestock species [ 12 , 13 , 14 ]. In livestock, the length of ROH segments serves as an indicator of the level of inbreeding, with longer ROH segments denoting recent inbreeding events and shorter segments indicating inbreeding that occurred earlier in the generations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the world's most popular commercial pig breeds, the Duroc pig has undergone intense artificial selection to improve its commercial productivity and product quality ( 1 ). In recent years, Duroc pigs have gained popularity as the terminal sire in many mixed commercial lean types due to their superior performance in growth, feed conversion efficiency and conformation, along with carcass and other beneficial characteristics ( 2 , 3 ). For example, Duroc × (Landrace × Yorkshire) (DLY) commercial pigs account for the majority of the current hog production market in China.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [ 11 ] found some candidate selection signatures within the DSE pig population were detected through the ROH islands. Wang et al [ 12 ] used Duroc (American origin) and Duroc (Canadian origin) pigs to investigate the harmful ROH regions on five economic traits. Xu et al [ 13 ] described the occurrence and distribution of ROH in the genome of Jinhua pigs and found several genes within ROH.…”
Section: Introductionmentioning
confidence: 99%